Clinical and Imaging Features of Desmoplastic Fibroma of Bone for Correct Diagnosis and Differentiation - Zhang, Zu-zhuo; Cao, Lei; Zhong, Zhi-Wei; Guo, Zhe; Wu, Hui-Zhao; Wu, Wen-Juan; Gao, Bu-Lang (Current Medical Imaging, 2022)
Objective: The objective of this study is to analyze the clinical and imaging features of desmoplastic fibroma of bone (DFB) for correct diagnosis. Materials and Methods: Twenty patients with DFB confirmed by pathology were enrolled, and the imaging presentations were analyzed. Among 20 patients, plain X-ray was performed in all patients, computed tomography (CT) was performed in 12, and magnetic resonance imaging (MRI) was conducted on eight. The clinical and imaging presentations were analyzed and classified to assist in correct diagnosis. Results: Twenty patients with DFB were retrieved, including eleven males and nine females with an age range of 2-52 years (median 27). The DFB involved the femur in six patients, ilium in five, tibia in four, humerus in two, lumbar vertebra in one, radius in one, and calcaneus in the remaining one. DFB was common in the metaphysis of long bones and could involve the diaphysis and epiphysis. The imaging presentations were divided into four types: the cystic expansile destruction in ten patients, osteolytic destruction in five, mixed destruction in four, and paraosseous destruction in one. CT value was 30 -60 Hu in the lesion area (6 cases CT value>45Hu). In eight patients with MRI scanning, the lesion in five patients presented with unevenly equal or low signal on T1WI and unevenly equal or high signal on T2WI, with irregular stripes or patches of low signal on both T1WI and T2WI. In the rest three patients, the lesion was evenly equal or low signal on T1WI and evenly high signal on T2WI. MRI more clearly showed a mass in the adjacent soft tissue and the range of edema in the DFB lesion. Conclusion: DFB is a rare tumor with strong local aggressiveness, cystic bone destruction, formation of tumor bone trabeculae, soft tissue masses on imaging presentations, low signals on T1WI and T2WI in the lesion, but no periosteal reaction or calcification, which are helpful for diagnosis of the disease and differentiation from other ones.
Keywords: Bone tumor